Shared Prosperity : Paving the Way in Europe and Central Asia - Bussolo, Maurizio (Washington, DC: World Bank, 2014)
The World Bank has recently defined two strategic goals: ending extreme poverty and boosting shared prosperity. Shared prosperity is measured as income growth among the bottom 40 percent of the income distribution in the population. The two goals should be achieved in a way that is sustainable from economic, social, and environmental perspectives. Shared Prosperity: Paving the Way in Europe and Central Asia focuses on the second goal and proposes a framework that integrates both macroeconomic and microeconomic elements.